A comparison of the biochemical parameters and micronutrient concentrations in the leaves of two Balkan endemic Scilla species from a karst area - Siniša Škondrić; Biljana Kukavica; Tanja Trifković; Dijana Mihajlović (Comprehensive Plant Biology)
Karst areas represent challenging habitats for plants, confronting plants with various abiotic and biotic stresses. This study aimed to compare the concentrations of certain primary (photosynthetic pigments and proteins) and secondary metabolites (phenolic compounds) and essential metals: iron (Fe), copper (Cu), zinc (Zn), manganese (Mn), and nickel (Ni) between the two Balkan endemic Scilla species: S. lakusicii and S. litardierei inhabiting karst areas. The metal concentrations in the leaves and soil were determined by atomic absorption spectrometry, while the concentrations of metabolites were determined spectrophotometrically. Significant differences were observed both between the localities and the plant leaves. The concentrations of metals in the leaves of S. lakusicii were: Fe 63.8 mg/kg; Zn 46.6 mg/kg; Mn 23.2 mg/kg; Cu 6 mg/kg and Ni 0.757 mg/kg, and in the leaves of S. litardierei: Fe 140 mg/kg; Zn 33.46 mg/kg; Mn 25.2 mg/kg; Cu 3.6 mg/kg and Ni 0.963 mg/kg. The concentration of soluble proteins in the leaves of S. lakusicii was 2.936 mg/g, compared to 3.459 mg/g in S. litardierei, while the concentration of phenolic compounds was 5.803 mg GAE/g in the leaves of S. lakusicii and 6.28 mg GAE/g in S. litardierei. The Chla/b ratio was slightly higher in the S. litardierei leaves, 1.8 compared to 1.63 in S. lakusicii. However, a significantly higher ratio of Chl (a+b)/Car (4.4) was measured in the leaves of S. litardierei compared to (2) in S. lakusicii. The differences in the concentrations of primary and secondary metabolites observed between the two Scilla species may be attributed to the influence of the habitat. The results are discussed in relation to the role of the analysed metabolites in the adaption of the two Scilla species to the karst environment.